Public Communication of Territorial Apparatus in the Implementation of Urban Community Development Policies - Delli Yudha Adi Nurcahyo; Hasan Sazali (Social Science Academic, 2026)
This study aims to analyze the communication practices of the Military District Command (Kodim) in fostering urban communities, communication strategies in conveying social security messages, the role of public communication by territorial officials in managing local issues, and efforts to build synergy between territorial officials and Medan residents in implementing urban community development policies. The study used a qualitative approach with library research methods and a case study of Medan City. Data were obtained from scientific journals, books, policy documents, institutional reports, and various publications relevant to public communication, TNI social communication, social security, and urban community development. Data analysis was conducted through content analysis and thematic analysis to identify key themes related to the research focus. The results show that the communication practices of the Military District Command (Kodim) in fostering urban communities are carried out through social communication, community dialogue, outreach, interpersonal communication with Babinsa (village supervisory officers), and the use of digital media. The social security communication strategy is implemented through persuasive, educational, participatory, and dialogical approaches aimed at increasing public awareness of various social threats. Public communication by territorial officials also plays a role in early detection of potential conflicts, managing information, clarifying local issues, and building coordination with various stakeholders. Synergy between territorial officials and residents is built through inclusive, transparent, and trust-based communication, thereby strengthening community participation and urban social resilience. The synthesis of studies yielded a collaborative public communication model encompassing social development, social security education, local issue management, and community partnership building.